2018
DOI: 10.3389/fphys.2018.01564
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Training on Quality of Life, Aerobic Capacity, and Cardiac Function in Older Patients With Heart Failure: A Meta-Analysis

Abstract: Aim: The purposes of this meta-analysis were to quantify the effectiveness of physical training on quality of life (QoL), aerobic capacity, and cardiac functioning in older patients with heart failure (HF) and evaluate dose–response relationships of training variables (frequency, volume, and duration).Methods: Scholarly databases (e.g., PubMed/MEDLINE, Google Scholar, and Scopus) were searched, identifying randomized controlled trials that investigated the effectiveness of different training modes on QoL (asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 63 publications
2
20
0
1
Order By: Relevance
“…In particular, the glucoregulatory system that is characterized by important bio-molecules such as glucagon and insulin is critical to maintain the constancy of glucose in the internal milieu. While it is clear that exercise training improves fitness and physical capacity in older adults [15,16,17,18,19], whether exercise can improve the hormonal profiles of older adults remains contentious [20,21,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the glucoregulatory system that is characterized by important bio-molecules such as glucagon and insulin is critical to maintain the constancy of glucose in the internal milieu. While it is clear that exercise training improves fitness and physical capacity in older adults [15,16,17,18,19], whether exercise can improve the hormonal profiles of older adults remains contentious [20,21,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A structured form was used to extract data by two authors. According to some meta-analyses [ 19 , 20 ] and the included studies, training prescription variables were grouped into the following areas: (i) characteristics of participants: health status (healthy vs. unhealthy) and gender (male vs. female vs. combined) and (ii) training prescription variables including training duration in weeks (<13 vs. ≥13 weeks), weekly training frequency (3 vs. 4–5 sessions per week), and session duration (20–30 min vs. 31–45 min vs. 46–65 min).…”
Section: Methodsmentioning
confidence: 99%
“…Since the values of the training prescription variables (namely, training duration in weeks, weekly training frequency, and session duration) varied among the studies, cut-off/threshold values were identified based on median values and previous meta-analysis [ 19 ] to allow comparing the various studies.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis that included studies on older patients demonstrated a positive effect of physical training on QoL and aerobic capacity regardless of the ET protocols ( 78 ).…”
Section: Special Populationsmentioning
confidence: 99%